2020
DOI: 10.3389/fpls.2020.00246
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the Difference Between Lumens and Scalariform Perforation Plates in Impeding Water Flow in Single Xylem Vessels and Vessel Networks in Cotton

Abstract: The geometrical structure and spatial arrangement of lumens, bordered pits, and scalariform perforation plates in xylem vessels modulate water flow from roots to leaves. Understanding their respective hydraulic functions is essential to unveil how plants regulate their hydraulic networks to facilitate the ascent of sap under biotic and abiotic stresses but is challenging because of the opaque nature of the vessel networks and water flow within them. We made the first-ever effort to discern the difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The utility of reduced root axial conductance capacity for late season soil water conservation in wheat has been further supported in recent work (Hendel et al, 2021). There may also be the possibility for longitudinal adjustments of xylem conduits (Meunier et al, 2017), regulation at the root to shoot junction (Meunier et al, 2018), as well as among the various attributes of protoxylem and metaxylem vessels, their pits (Xu et al, 2020) or perforation plates (Gao et al, 2020b). These may be part of a suite of embolism response traits and do not preclude the possibility that embolism is itself a means of restricting transpiration (McCully, 1999), in which aquaporins play a key recovery role (Secchi et al, 2017).…”
Section: Root Conductancementioning
confidence: 93%
“…The utility of reduced root axial conductance capacity for late season soil water conservation in wheat has been further supported in recent work (Hendel et al, 2021). There may also be the possibility for longitudinal adjustments of xylem conduits (Meunier et al, 2017), regulation at the root to shoot junction (Meunier et al, 2018), as well as among the various attributes of protoxylem and metaxylem vessels, their pits (Xu et al, 2020) or perforation plates (Gao et al, 2020b). These may be part of a suite of embolism response traits and do not preclude the possibility that embolism is itself a means of restricting transpiration (McCully, 1999), in which aquaporins play a key recovery role (Secchi et al, 2017).…”
Section: Root Conductancementioning
confidence: 93%
“…The importance of root traits in water uptake has been intensively studied over the past decades (Javaux et al, 2013;Lynch, 2013;Lynch, 2019;Postma et al, 2014), but Fig. 5 shows that other factors are equally important in mediating root water uptake and should be considered in screening drought-tolerant varieties (Gao et al, 2020;Sun et al, 2021;Wang et al, 2020).…”
Section: Root Water Uptakementioning
confidence: 99%
“…The origin of the isotopes flowing through the stem (hence its associated water) can be tracked down to soil based on mass balance (Brooks et al, 2010;Liu et al, 2021;Ma and Song, 2016;Schwendenmann et al, 2015). While isotope method has been widely used, it neglects that the movement of isotopes from the location they are taken from soil to the location in the stem where they are sampled is not a convective process as presumed by the mass-balance method; they mixes with isotopes taken by roots from other places in the soil due to interconnectedness of the xylems and variation of water velocities in and between the xylems (Ehleringer and Dawson, 1992;Gao et al, 2020). Apart from these hydrodynamic mixings, there are other error sources that affect the isotope method (von Freyberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2001; Sperry et al ., 2006; Christman & Sperry, 2010), in other work, the Hagen-Poiseuille lumen resistivity is much less than the measured value, suggesting a significant effect of perforation plates on axial conductance (Sperry et al ., 2005). For example, Gao et al ., (2020) found that estimates of hydraulic conductance in xylem vessels of cotton calculated from the Hagen-Poiseuille equation were overestimated by more than 200%, largely due to the inability of the equation to represent perforation plates. Ultimately, the hydraulic resistance of these perforation plates is a function of their structure and the distance between successive plates along the length of the conduit, or the length of the vessel elements (Fig.…”
Section: Introductionmentioning
confidence: 99%